1988
DOI: 10.1007/bf00380021
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between cell fate and the distribution of proteins that are synthesized before the midblastula transition in Xenopus

Abstract: The proteins synthesized before the 512-cell stage by Xenopus blastomeres with different fates were compared by one dimensional PAGE. Blastomeres that contributed more progeny to antero-dorsal axial structures produced proportionately more of two proteins of 225000 and 245000 daltons. Additionally, these proteins were reversibly increased in ventralized embryos and were decreased in dorsalized embryos. These observations indicate that some proteins that are synthesized during cleavage stages are expressed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It is most interesting that there are reports of cleavage stage posttranscriptional differences between 16-cell blastomeres. Protein synthesis studies identified unique protein bands/spots from dorsal versus ventral animal 16-and 32-cell blastomeres (Klein and King, 1988;Miyata et al, 1987). A recent proteomic analysis showed that Gmnn protein is significantly enriched in D11 versus V11 blastomeres (Lombard-Banek et al, 2016), and D11 and V11 blastomeres have metabolite differences that affect cell fate decisions (Onjiko et al, 2015).…”
Section: Neural Fate "Bias" Is Not Due To Differences In Maternal Tramentioning
confidence: 99%
“…It is most interesting that there are reports of cleavage stage posttranscriptional differences between 16-cell blastomeres. Protein synthesis studies identified unique protein bands/spots from dorsal versus ventral animal 16-and 32-cell blastomeres (Klein and King, 1988;Miyata et al, 1987). A recent proteomic analysis showed that Gmnn protein is significantly enriched in D11 versus V11 blastomeres (Lombard-Banek et al, 2016), and D11 and V11 blastomeres have metabolite differences that affect cell fate decisions (Onjiko et al, 2015).…”
Section: Neural Fate "Bias" Is Not Due To Differences In Maternal Tramentioning
confidence: 99%
“…The nature and identities of these dorsal determinants are not currently well defined. Previous experiments have shown that these putative cytoplasmic factors may be mRNA or proteins ( Klein and King, 1988 , Miyata et al, 1987 , Shiokawa et al, 1984 ). Further, it has been argued that cytoplasmic polyadenylation may be the mechanism for the change in dorsal inducing activity of total RNA isolated from the dorsal lineage between the 8- and 16-cell stages ( Pandur et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%